Physiological and Microscopic Characterization of Cyclic-di-GMP-Mediated Autoaggregation in Erwinia amylovora - Kharadi, Roshni R.; Sundin, George W. (Frontiers in Microbiology, 2019)
The second messenger cyclic-di-GMP (c-di-GMP) is a critical regulator of biofilm formation in the plant pathogen Erwinia amylovora. Phosphodiesterase (PDE) enzymes are responsible for the degradation of intracellular c-di-GMP. Previously, we found that the deletion of one or more of the three PDE enzyme encoding genes (pdeA, pdeB, and pdeC) in E. amylovora Ea1189 led to an increase in biofilm formation. However, in mutants Ea1189ΔpdeAC and Ea1189ΔpdeABC, biofilm formation was reduced compared to the other single and double deletion mutants. Here, we attribute this to an autoaggregation phenotype observed in these two mutants. Examination of Ea1189ΔpdeABC cellular aggregates using scanning electron microscopy indicated that a subset of cells were impaired in cell separation post cell division. Concomitant with this phenotype, Ea1189ΔpdeABC also exhibited increased transcription of the cell-division inhibitor gene sulA and reduced transcription of ftsZ. Ea1189ΔpdeABC showed a significant reduction in biofilm formation, and biofilms formed by Ea1189ΔpdeABC exhibited a distinctive morphology of sparsely scattered aggregates rather than an evenly distributed biofilm as observed in WT Ea1189. Our results suggest that highly elevated levels of cyclic-di-GMP lead to increased cell-cell interactions that contribute to autoaggregation and impair cell-surface interaction, negatively affecting biofilm formation.